2016
DOI: 10.1186/s12885-016-2521-9
|View full text |Cite
|
Sign up to set email alerts
|

New anti-cancer chemicals Ertredin and its derivatives, regulate oxidative phosphorylation and glycolysis and suppress sphere formation in vitro and tumor growth in EGFRvIII-transformed cells

Abstract: BackgroundEGFRvIII is a mutant form of the epidermal growth factor receptor gene (EGFR) that lacks exons 2–7. The resulting protein does not bind to ligands and is constitutively activated. The expression of EGFRvIII is likely confined to various types of cancer, particularly glioblastomas. Although an anti-EGFRvIII vaccine is of great interest, low-molecular-weight substances are needed to obtain better therapeutic efficacy. Thus, the purpose of this study is to identify low molecular weight substances that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Colonies were washed 3 times in PBS, fixed in methanol, stained with 0.1% crystal violet, and counted using an inverted microscope. To examine anchorage-independent 3D growth, MDA-MB-231 cells stably expressing pCDH and HA-FBXO22 (500 cells in 2 mL media) were seeded on 24-well ultra-low attachment surface plates (Corning) as described previously (29). After 2 weeks of culture, cells were observed and counted under a phase-contrast microscopy.…”
Section: Gst Pull-down Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Colonies were washed 3 times in PBS, fixed in methanol, stained with 0.1% crystal violet, and counted using an inverted microscope. To examine anchorage-independent 3D growth, MDA-MB-231 cells stably expressing pCDH and HA-FBXO22 (500 cells in 2 mL media) were seeded on 24-well ultra-low attachment surface plates (Corning) as described previously (29). After 2 weeks of culture, cells were observed and counted under a phase-contrast microscopy.…”
Section: Gst Pull-down Assaymentioning
confidence: 99%
“…S1D). Anchorage-independent 3D growth assays (29) showed that overexpression of FBXO22 in MDA-MB-231 cells increased the size but not number of formed spheroidal clumps ( Supplementary Fig. S1E and S1F).…”
Section: Fbxo22 Enhances Cell Proliferation In Vitro and Tumor Growthmentioning
confidence: 99%
“…Previous studies also indicated that Ertredin inhibits ATP synthesis to inhibit cell proliferation. 5,6 Indeed, NDUFA12 knockdown reduced the NDUFA12 expression levels, resulting in the suppression of cell proliferation (Figure 5F). Taken together, these results suggest that NDUFA12 is a biologically relevant target of Ertredin and is responsible for its antiproliferative activity in cancer cells.…”
Section: Biological Validation Of Ndufa12 As a Target Of Ertredinmentioning
confidence: 96%
“…Ertredin exhibited potent anticancer activity against EGFRvIII-derived cancer cells. 5,6 However, it is unclear how Ertredin exerts an inhibitory effect on these cells. To address this question and identify the target of Ertredin, we first examined the effect of Ertredin on the proliferation of various cultured cells.…”
Section: Ertredin Shows Potent Anticancer Activity In Hepg2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation